The Failed Integration of Persona and Shadow in Coralie Fargeat’s The Substance - Ielma Maulidiah; Hariyono; Cahyaningsih Pujimahanani (Menulis: Jurnal Penelitian Nusantara, 2026)
This study examines the failure of integration between persona and shadow as reflected in the characters of Elisabeth Sparkle and Sue in Coralie Fargeat’s The Substance. The research applies Carl Gustav Jung’s theory of persona, shadow, and the process of individuation to analyze how psychological imbalance can lead to identity fragmentation, moral collapse, and loss of agency. The data are drawn from selected dialogues and scenes in the film script. The findings indicate that Elisabeth’s refusal to recognize Sue as a part of herself, along with Sue’s position as a shadow that refuses to respect the required balance and continually seeks dominance without restraint, results in psychological division rather than wholeness. Instead of achieving integration, the repression of the shadow leads to destruction. Ultimately, the film presents a tragic portrayal of what happens when a person clings too tightly to a social mask and refuses to confront the hidden aspects of the self.